2020
DOI: 10.7759/cureus.9802
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic Liver Abscess and Sepsis Caused by Streptococcus constellatus in the Immunocompetent Host

Abstract: Streptococcus constellatus is a member of Streptococcus milleri group which is a subgroup of Viridans streptococci, first described by Guthof in 1956 after being isolated from dental abscesses. S. constellatus, a gram positive, non-sporing, non-motile, catalase negative cocci, is the normal flora of the oropharyngeal, gastrointestinal and urogenital tract. It is not a commonly encountered pathogen but has a propensity to form abscesses and cause bacteremia in the immunocompromised patient. Here, we report a 78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Moreover, qRT-PCR also showed that the mRNA levels of IL-1β, IL-6, TNF-α, and MCP-1 in the liver were higher in the MD+KLA mice. Clinically, ALT, AST, and LDH are commonly used to evaluate liver function, 35 and they are elevated in liver abscess patients. In this study, ALT was significantly elevated in KLA mice, and the difference was even more pronounced in MD+KLA mice.…”
mentioning
confidence: 99%
“…Moreover, qRT-PCR also showed that the mRNA levels of IL-1β, IL-6, TNF-α, and MCP-1 in the liver were higher in the MD+KLA mice. Clinically, ALT, AST, and LDH are commonly used to evaluate liver function, 35 and they are elevated in liver abscess patients. In this study, ALT was significantly elevated in KLA mice, and the difference was even more pronounced in MD+KLA mice.…”
mentioning
confidence: 99%
“…It has been observed that bacteremia occurs most often after a tooth or soft tissue infection (4). It is presumed that immunocompromised patients, such as those with diabetes mellitus, chronic kidney disease, hepatobiliary disease, neoplasias, or undergoing chemotherapy, are at higher risk of bacteremia (8). Our patient was not immunocompromised.…”
Section: Discussionmentioning
confidence: 86%
“…Recent studies have found that S constellatus usually exacerbates inflammation in association with other anerobic organisms and gram-negative pathogens, especially in healthy individuals . [ 7 , 8 ] Treatment with broad-spectrum antibiotics and anti-anaerobic antibiotics is essential. Our patient had neither predisposing factors nor an underlying disease as described above and his blood culture, sputum culture, and pus culture showed no anaerobic bacteria.…”
Section: Discussionmentioning
confidence: 99%